Children and adolescents in a situation of social vulnerability in Brazil (Research, Society and Development, 2022)
The theme of this paper is Children and Adolescents in a situation of social vulnerability in Brazil. The objective of the present work is to make an analysis on the situation of social vulnerability in our country, through the study of the concepts of social vulnerability, life in society and on the meaning of human dignity, in order to understand what the situation is of social vulnerability, as well as the ways to detect it, the pictures as it appears in our daily lives. The theme studied in this paper is extremely relevant to society and our current legal system, considering that, once the situation experienced by children and adolescents in Brazil is understood, the situation can be avoided both through policies to improve infrastructure, when improvement in the school and family environment, contributing to a better understanding of the application of the Statute of the Child and Adolescent in cases of need for family leave, as a way to help children and adolescents who are at risk and still preserve the future of our nation. For the development of this work, the current doctrine and legislation on the subject were analyzed, and from these, the considerations on the theme presented here were presented.